2011
DOI: 10.1182/blood-2010-07-296921
|View full text |Cite
|
Sign up to set email alerts
|

The dominant negative β isoform of the glucocorticoid receptor is uniquely expressed in erythroid cells expanded from polycythemia vera patients

Abstract: Glucocorticoid receptor (GR) agonists increase erythropoiesis in vivo and in vitro.To clarify the effect of the dominant negative GR␤ isoform (unable to bind STAT-5) on erythropoiesis, erythroblast (EB) expansion cultures of mononuclear cells from 18 healthy (nondiseased) donors (NDs) and 16 patients with polycythemia vera (PV) were studied. GR␤ was expressed in all PV EBs but only in EBs from 1 ND. The A3669G polymorphism, which stabilizes GR␤ mRNA, had greater frequency in PV (55%; n ‫؍‬ 22; P ‫؍‬ .0028) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 55 publications
(100 reference statements)
6
36
0
Order By: Relevance
“…The impedimentary action of GR␤ on GR␣ was recently demonstrated by Varricchio et al in polycythemia vera (PV) patients, which have increased erythroid cell growth (42). This study found that PV patients have a polymorphism in the human GR gene that leads to the stabilization of the GR␤ mRNA, resulting in higher protein levels.…”
Section: Discussionsupporting
confidence: 48%
“…The impedimentary action of GR␤ on GR␣ was recently demonstrated by Varricchio et al in polycythemia vera (PV) patients, which have increased erythroid cell growth (42). This study found that PV patients have a polymorphism in the human GR gene that leads to the stabilization of the GR␤ mRNA, resulting in higher protein levels.…”
Section: Discussionsupporting
confidence: 48%
“…7 In this issue of Blood, we describe that the frequency of the A3669G SNP is increased in polycythemia vera (PV; 55%) and that erythroblasts expanded in vitro from these patients express GR␤ and do not respond to corticosteroids. 8 Based on these and other observations, we suggest that GR␤ may represent a "host genetic modifier" that in combination with JAK2 mutations determines erythrocytosis.…”
Section: Increased Frequency Of the Glucocorticoid Receptor A3669g (Rmentioning
confidence: 99%
“…10 Clinical management of DBA includes corticosteroid therapy and for the 40% of patients who, for reasons still to be understood, do not respond to corticosteroids, red cell transfusions and/or hematopoietic stem cell transplantation. 11 The increased frequency of the A3669G SNP in PV patients whose erythroid cells did not respond to corticosteroids in vitro 8 prompted us to determine the frequency of this SNP in DBA patients. A total of 58 patients were analyzed, of whom 86% (n ϭ 50) presented mutations in RPL5, RPL11, RPS19, and RPS26.…”
Section: Increased Frequency Of the Glucocorticoid Receptor A3669g (Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncogenic receptor AR variants(Pca) [24][25] ; ER pro-neoplastic signaling [26][27] , neoplastic ESR1-CCDC170 fusion(also oncogenic receptor ERalpha fusion)(breast cancer) 7,28 ;GRβ aberrant signaling(Cushing's disease,erythrocytosis, GR + breast cancer, Nelson's syndrome) [29][30][31] ; FSH/FSH receptor oncogenic signaling(preneoplastic ovarian surface epithelial cells)…”
Section: Steroid Receptorsmentioning
confidence: 99%